2020
DOI: 10.1016/s0140-6736(20)30746-7
|View full text |Cite
|
Sign up to set email alerts
|

First-wave COVID-19 transmissibility and severity in China outside Hubei after control measures, and second-wave scenario planning: a modelling impact assessment

Abstract: Purpose: The notorious COVID 19 pandemic has caused rapid and drastic changes in cancer care all over the world in 2020. This online survey aims to assess the extent to which the pandemic has affected cancer care in gynecological oncology amongst members of Association of Gynecological Oncologists of India (AGOI), a registered professional society, founded in 1991. Methods: We developed and administered a cross-sectional, flash survey to members of The Association of Gynecological Oncologists of India (AGOI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
810
1
24

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(866 citation statements)
references
References 20 publications
31
810
1
24
Order By: Relevance
“…Our results are concordant with 3 studies from China, 29-31 which reported no evidence for an association of epidemic growth with temperature and relative humidity, 29 but strong decreases in epidemic growth associated with public health measures. 30,31 A recent rapid systematic review concluded that the evidence to support national closure of schools to combat COVID-19 is very weak and that data from influenza outbreaks suggest that school closures could have relatively small effects on SARS-CoV-2 owing to its high transmissibility and apparent low clinical effect on school children. 32 Our results suggest that school closures are likely to have a larger effect than suggested in this review, but the clustering of school closures with other public health interventions means that we were unable to reliably estimate the independent effect of this intervention on the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are concordant with 3 studies from China, 29-31 which reported no evidence for an association of epidemic growth with temperature and relative humidity, 29 but strong decreases in epidemic growth associated with public health measures. 30,31 A recent rapid systematic review concluded that the evidence to support national closure of schools to combat COVID-19 is very weak and that data from influenza outbreaks suggest that school closures could have relatively small effects on SARS-CoV-2 owing to its high transmissibility and apparent low clinical effect on school children. 32 Our results suggest that school closures are likely to have a larger effect than suggested in this review, but the clustering of school closures with other public health interventions means that we were unable to reliably estimate the independent effect of this intervention on the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…NPIs have been linked to the spread of SARS-CoV-2 primarily within or from a single country [8][9][10][11][12][13][14][15][16][17][18][19] , mostly focusing on the novel coronavirus outbreak in China. The majority of findings are based on transmission models where epidemiological parameters are informed by previous studies or corroborated via simulation.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, once an outbreak is underway, the timevarying effective reproduction number 'R t ' is more relevant as it tracks the subsequent changes in transmission, and can thus be used to monitor the efficacy of control measures and adjust them accordingly. [6][7][8] However, any given transmission event is reflected in the data only after a delay, which must be accounted for in the estimation of such indicators for accurate interpretation. 7 Previous studies have shown that a severe epidemic with R 0~2 •4 can be contained by combining effective quarantine, behavioral change to reduce social mixing, targeted antiviral prophylaxis, and prevaccination.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, in the absence of targeted therapeutics and vaccination for COVID19, an unprecedented onethird of the world's population is currently under lockdowns -with the primary target of reducing the R t below the threshold of 1. 6,9 India responded to the COVID19 pandemic rapidly and decisively by imposing a nationwide lockdown on 25 March 2020, when there were 536 cases and 10 deaths. 3,10 This 'suppression strategy', though effective, has its limitations the social and economic cost of such populationwide social distancing is huge, which limits the longterm implementation of these measures.…”
Section: Introductionmentioning
confidence: 99%